Aplikasi Akademik SMK Negeri 1 Sawit Boyolali Berbasis Website - Ya'kub, Rifki, Fajar Suryawan, S.T., M.Eng.Sc, Ph.D (2016)
Educational institutions especially SMK Negeri 1 Sawit Boyolali Vocational High School is located at Jalan Raya Solo-Jogja KM 15 Bendosari, District of sawit, Boyolali. Currently SMK Oil Boyolali been using computer technology but the use is not maximized most of the work of the academic is still done by recording so that the app requires an academic to facilitate the processing associated with the school's academic applications made the results of the use of the programming language PHP framework CodeIgniter and MySQL database. While the method of making an application using waterfall method that has sustained in to do. The purpose of this thesis is to create an academic application that is able to provide the means and facilities to teachers and students in knowing the teaching schedule, timetable and presence of students easily and quickly. This research was conducted with the waterfall method starting from a needs analysis. The test results through testing blackbox application and by giving questionnaires to respondents it can be concluded that the application can run well.